2015
DOI: 10.1515/orhu-2015-0002
|View full text |Cite
|
Sign up to set email alerts
|

Provisioning nest material for Rooks; a potential tool for conservation management

Abstract: Active conservation measures often entail supplementing scarce resources, such as food or nesting site to high conservation value species. We hypothesized that adequate nest material in reasonable distance is a scarce resource for Rooks breeding in open grassland habitats of Hungary. Here we show that Rooks willingly utilize large quantities of provided excess nesting material, and that this procedure may alter nest composition, and increase the number of successful pairs. Our results show that while nest heig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
5
1
Order By: Relevance
“…The result being non-significant in the case of nest height could be caused by the smaller sample of compared nests. Horváth et al (2015) did not study the width of nests, but in contrast to our results they did not record a significant impact of the supporting activity on the height of nests. From their results it is evident that the provisioned material was used to build each nest in the supported colony, where the rooks used the twigs with a significantly larger diameter for building nests.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The result being non-significant in the case of nest height could be caused by the smaller sample of compared nests. Horváth et al (2015) did not study the width of nests, but in contrast to our results they did not record a significant impact of the supporting activity on the height of nests. From their results it is evident that the provisioned material was used to build each nest in the supported colony, where the rooks used the twigs with a significantly larger diameter for building nests.…”
Section: Discussioncontrasting
confidence: 99%
“…With a longterm perspective, in some species a gradual change in of rooks with nest material as a potential tool for stabilizing colonies and increasing nesting opportunities in the countryside. Project report preference of local or entire populations from nesting in the original, natural conditions to nesting in artificial conditions may be shown (Bartolotti 1994, Chavko et al 2014, Kotymán et al 2015. In increasing and improving the nesting conditions, emphasis is put on hollow-nesting birds or species nesting in nest boxes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such sites may offer differing support from below and may be reflected in the strength and rigidity of the materials used in the nest base. Interestingly, Horváth et al (2015) showed that nests constructed high in trees by Rooks Corvus frugilegus, contain woody stems that average around 5 mm in diameter (range 2-15 mm). This may reflect the much larger body mass of this corvid [420-490 g (Dunning 2008)].…”
Section: Discussionmentioning
confidence: 99%
“…Small warblers (Sylvidae) and wagtails (Motacillidae) also rarely use woody stems in their nests (Dickinson, Locke, Goodman and Deeming, unpublished data 2018). Along with Rooks (Horváth et al 2015) other corvids, e.g. Eurasian Jays Garrulus glandarius and Carrion Crows Corvus corone, are from two to five times heavier than thrushes and also build nests largely made of woody materials (Kulczycki 1973;Ferguson-Lees et al 2011).…”
Section: Discussionmentioning
confidence: 99%